30 years from Dayton: Analysis of proposals for constitutional changes in Bosnia and Herzegovina - Lozo, Nikolina (Political Life, 2025)
The Dayton Peace Agreement was signed in Paris in December 1995. The Agreement ended the war and established a new constitutional and political system. After the first decade, there was a talk of the need to change the Agreement. This refers primarily to the amendments to the Constitution, which is integral to the Peace Agreement. Main research question relates to the proposals for constitutional changes in Bosnia and Herzegovina and the impact on the political system. This question arises from the observed demand for constitutional change, which didn’t happen thirty years after the signing of the agreement. Methodology involves a comparative analysis of the three most significant proposals: The April Package, the Prud Agreement, and the Butmir Process. In addition, the statements and interviews of political representatives during and after the negotiation process and their interpretation of the agreements reached will be used. This paper contributes to understanding the constitutional reform process and its challenges. The paper gives us a new perspective on understanding constitutional changes in Bosnia and Herzegovina. Ultimately, this paper represents a significant theoretical framework for future research.